Inside the box : a proven system of creativity for breakthrough results - Boyd, Drew. (Simon & Schuster, 2014)
"This counterintuitive and powerfully effective approach to creativity demonstrates how every corporation and organization can develop an innovative culture. The traditional attitude toward creativity in the American business world is to "think outside the box"--to brainstorm without restraint in hopes of coming up with a breakthrough idea, often in moments of crisis. Sometimes it works, but it's a problem-specific solution that does nothing to engender creative thinking more generally. Inside the Box demonstrates Systematic Inventive Thinking (SIT), which systemizes creativity as part of the corporate culture. SIT requires thinking inside the box, working in one's familiar world to create new ideas independent of specific problems. Dozens of books discuss how to make creative thinking part of a corporate culture, but none takes the innovative and unconventional approach of Inside the Box. SIT's techniques and principles have instilled creative thinking into such companies as Procter & Gamble, Johnson & Johnson, and other industry leaders. Inside the Box shows how corporations have successfully used SIT in business settings as diverse as medicine, technology, new product development, and food packaging. With "inside the box" thinking, companies of any size can become sufficiently creative to solve problems even before they develop and to innovate on an ongoing basis. It works!"--